2008
DOI: 10.1007/s00394-008-2006-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of combined action of different chemopreventive dietary compounds

Abstract: Consumption of fruits and vegetables has generally been associated with a decrease in cancer incidence and cardiovascular disease. Over the years, numerous bioactive compounds have been identified that contribute to these beneficial health effects. More recently, evidence is emerging that specific combinations of phytochemicals may be far more effective in protecting against cancer than isolated compounds. Combinatorial effects have been observed where any one of the single agents is inactive. Apart from inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(168 citation statements)
references
References 67 publications
2
163
0
3
Order By: Relevance
“…There remains the indefinite yet unending possibility that there exists better preventive or therapeutic potential in the synergistic action of these terpenoid molecules. Emerging studies have shown that a combination of phytochemicals may be more effective against cancer than individual components [187][188][189][190][191] . Further studies are needed to explore the full potential of these multifunctional terpenoids in the combinational setting.…”
Section: Resultsmentioning
confidence: 99%
“…There remains the indefinite yet unending possibility that there exists better preventive or therapeutic potential in the synergistic action of these terpenoid molecules. Emerging studies have shown that a combination of phytochemicals may be more effective against cancer than individual components [187][188][189][190][191] . Further studies are needed to explore the full potential of these multifunctional terpenoids in the combinational setting.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that in addition to antioxidant activity, phenolic compounds perform other actions in the organism, such as vasodilator, anti-inflammatory, anti-atherogenic and antithrombotic and also act as modulators of enzymatic pathways, of gene expression, improve the properties of cell membrane and receptors function [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, polyphenols are investigated as promising medicinal agents for the treatment of bacterial infections, ulcer, hypertension, vascular fragility, allergies, hypercholesterolemia and, most notably, various types of cancer. While a number of literature reviews have addressed the anticancer properties of natural polyphenols (see references [1][2][3][4]), targeting protein kinases with these compounds has not received its due attention in the review literature despite a large amount of original research reports indicating that this strategy holds an immense potential for the development of novel cancer therapies. Therefore, the aim of the present review is to fill this gap in the literature by focusing on polyphenols whose anticancer properties are mediated through specific kinase activity inhibition.…”
Section: Introductionmentioning
confidence: 99%